Effect of decreasing total N and increasing NH4+ in the fertigation formula of carnation crop (2018)
An alternative to nitrogen leaching in the cultivation of cut flowers is the optimization of the fertigation formula. In order to study the reduction of total nitrogen and the increase in the proportion of ammonium in the NH4+:NO3- ratio, two concentrations of total nitrogen were evaluated under greenhouse conditions (200-140 mg L-1 in the vegetative phase and 160-112 mg L-1 in the productive phase), along with three NH4:NO3- ratios (5:95, 15:85 and 25:75) in standard carnation cv. Don Pedro grown on substrate. The elementary contents of the plant tissue, the pH and the nitrate concentration in the leachate were determined at three times during the cultivation. Higher concentrations of Zn and Cu were observed in the plant tissue with the decrease in the total N; likewise, increases of N and Zn and a decrease of Mg were obtained with the increase in NH4+, which in turn decreased the pH in the substrate. The decrease in the total N did not significantly affect the content of N in the plant tissue, but did significantly affect the content of NO3- and total N in the leachate.